Factors Influencing Company Valuation in the Indonesian Cement Sector - Wangi, Risfa Mustifa; Putra, Okta Eka; Kusumawardhani, Aninditha Putri (Indonesian Scientific Publication, 2025)
Investigation elucidates the characterization and impact of IC, effective corporate governance, and environmental performance on corporate valuation within the cement industry. Empirical evidence reveals a deterioration in corporate valuation within the cement industry during the period spanning 2019 to 2023. Among the novel contributions distinguishing this research from antecedent studies is its targeted examination of companies within the cement industry, a focus that remains underexplored in existing literature. The methodology adopted is quantitative, utilizing both descriptive and verification approaches. The research population comprises all cement industry during the 2019-2023 period. Sample selection was executed through purposive sampling based on specified criteria, resulting in the acquisition of 25 financial reports from five distinct companies. The findings of this study indicate that IC, GCG, and Environmental Performance collectively exert an influence on Firm Value within cement industry companies on the IDX throughout the 2019-2023 timeframe. These findings suggest that enterprises exhibiting robust IC, adhering to sound corporate governance practices, and demonstrating commendable environmental performance are predisposed to achieving elevated firm value. Additionally, this research reveals that IC has the most pronounced effect on firm value, succeeded by Environmental Performance, whereas GCG appears to have an insubstantial impact. It is imperative for cement industry companies in Indonesia to adopt a comprehensive strategy aimed at enhancing firm value.